Handbook of Systems Biology: Concepts and Insights - A J Marian Walhout [editor] (Academic Press, 2013)
The Handbook of Systems Biology is an invaluable resource for understanding the interdisciplinary aspects of systems Biology for researchers in genetics, molecular biology, Cell biology, microbiology, and biomedical science.